2018
DOI: 10.1001/jamaophthalmol.2018.3488
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy With Programmed Cell Death 1 Inhibitors for 5 Patients With Conjunctival Melanoma

Abstract: onjunctival melanoma is a rare tumor with the potential to invade the eye, eyelid, and orbit and spread to regional lymphatics and distant sites, including the lungs, skin, liver, and brain. It was previously reported to have local recurrence rates of 36% to 45% at 5 years and 31% to 59% at 10 years. 1 Lymph node involvement was found in 19% of patients with conjunctival melanoma and systemic metastases were found in 19% of patients within 10 years after initial diagnosis. 1,2 Melanoma-related death was report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 14 publications
1
62
0
2
Order By: Relevance
“…Prescribing these drugs as neoadjuvants may help surgeons to achieve free surgical margins and may reduce or eliminate micro-metastases. Also immunotherapy (anti-PD-1) could be a valid neoadjuvant therapy, since it has recently shown encouraging results in locally advanced and metastatic conjunctival melanoma [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prescribing these drugs as neoadjuvants may help surgeons to achieve free surgical margins and may reduce or eliminate micro-metastases. Also immunotherapy (anti-PD-1) could be a valid neoadjuvant therapy, since it has recently shown encouraging results in locally advanced and metastatic conjunctival melanoma [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A small case series suggested that, like other mucous membrane melanomas, immunotherapy may be effective in the treatment of advanced local and metastatic conjunctival melanoma. 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…Sagiv et al, 2018). Notably, one of two patients with BRAF-mt CoM treated with a BRAF inhibitor in our institution responded well to treatment (unpublished).…”
mentioning
confidence: 86%